ERATOSFEN GʻALVIRI VA UNING MAKTAB DARSLIGIDAGI AHAMIYATI. - Doniyor Mirzoev Erkinovich (TADQIQOTLAR.UZ, 2024)
Abstract: Sieve of Eratosthenes is an algorithm for finding all prime numbers up to integer n, named after the ancient Greek mathematician Eratosthenes Cyrene. Eratosthenes Algorithm is the fastest way to find small prime numbers (typically less than 10 million).